Theoretical study on the atmospheric reaction of CH3SH with O2. Issue 5 (10th October 2018) - Bian, He; Xu, Bin; Zhang, Honghong; Wang, Qian; Zhang, Huiming; Zhang, Shiguo; Xia, Daohong
Abstract: A detailed study on the reaction mechanism of CH3 SH with O2 was carried out using quantum chemical methods. Eleven singlet pathways and four triplet pathways were found based on CCSD(T)//M06‐2x calculations. The nature of chemical bonding evolution was also studied using electron localization function and atoms in molecules analysis. Moreover, reaction rate constants were calculated between 200 and 800 K at the level of the transition state theory by Wigner tunneling correction. The results suggest that the main products should be CH2 SO, H2 O, CH3 OH, SO, CH4, and SO2, respectively, basically coinciding with the experimental results. The corresponding feasible pathways are channels R7, R8, and R9, respectively, with an effective energy barrier of 56.21 kJ/mol. Obviously, given the low energy barrier similar to the main paths mentioned above, the products CH2 SH and HO2 should assume a definite proportion in all possible products, although such species were not yet detected in experiment. Abstract : Sulfur compounds have important influences on the atmospheric environment and living organisms. The mechanism of the reaction of CH3 SH with O2 is explored by density functional theory calculations both on the singlet and triplet potential energy surfaces (PESs). This study suggests that the CH3 SH + O2 reaction is more favorable for the singlet PES, and the corresponding feasible product species include CH3 OH, SO, CH2 SO, H2 O, CH4, and SO2 .